Optimization of Employee Performance and Quality Service with Smart Office Implementation - Andi Isnaeni Hamzah; Andi Reni; Kasman Damang (Magister Management, Hasanuddin University, 2021)
This study aims to analyze and the influence of complementary, motivation, and use of information systems in improving performance and optimizing the quality of administrative services at the secretariat office of the government of South Sulawesi province with the application of smart offices. this type of research is quantitative, where this study uses survey methods with path analysis techniques. The data collected from 89 respondents using questionnaires given to 8 bureaus. On the basis of the findings, it indicated that competencies positively and significantly affect employee performance, but showing insignificant results when linking to service quality. Interestingly, information systems and motivation show a positive coefficient, but insignificant scores on employee performance and service quality. When evaluating employee performance as an intervening variable, competencies and information systems did show a significant score in relation to service quality, but it does for motivation.